PENGARUH TASK VISIBILITY TERHADAP SOCIAL LOAFING DENGAN EXCHANGE IDEOLOGY SEBAGAI VARIABEL PEMODERASI (Studi pada Karyawan Tetap PT BPR Surya Yudhakencana) - Amara Wafiq; Andriyani Andriyani (Diponegoro Journal of Management, 2022)
To sustain the effectiveness and productivity of employees, organizations need to avoid social loafing employees. Thus, it is considered important for this research to investigate antecedents of social loafing both individual (i.e., exchange ideology) and situational factors (i.e., task visibility). This research used a quantitative method and questionnaire as its research instrument to get the primary data using 90 employees as samples. SPSS PROCESS version 4.0 was used for testing the hypotheses. The output showed that task visibility is not significantly affecting social loafing (β = .054, t = .20, p ≥ .05). However, exchange ideology has been proven to significantly affecting social loafing (β = .740, t = 2.84, p ≤ .05). The test of the interaction between task visibility and exchange ideology toward employee social loafing showed that that indirect effect is not significantly affecting social loafing (β = -.118, t = -1.095, dan p ≥ .05). Accordingly, this study suggested that individual characteristics, especially exchange ideology, are important in reducing social loafing.